Fostering the Spirit Entrepreneurs in terms of Independent Young of Self Efficacy, Adversity Intelligence, and Education to Entrepreneurship Increase the Competitiveness of Universitas Bhayangkara Jakarta Raya - Dewi Sri Woelandari Pantjolo Giningroem; Ery Teguh Prasetyo; Novita Wahyu Setyawati (Majalah Ilmiah Bijak, 2021)
Efforts to instill the spirit and spirit of entrepreneurship in Indonesia, especially in Higher Education, are continuously encouraged and enhanced by various methods and strategies, so as to make students interested in entrepreneurship. Educational institutions that want to survive and excel in the field of education must have the courage to compete globally and be able to create or gain an advantage in competition. This study aims to determine the effect of self-efficacy, adversity intelligence, andeducation entrepreneurship in students of the Faculty of Economics, University of Bhayangkara Jaya Bekasi. This study uses a quantitative approach with the overall research object of the population (students of the Faculty of Economics, University of Bhayangkara Jaya Bekasi) who have taken entrepreneurship courses. Testing the question indicator is done by testing the validity and reliability testing. The analytical tools used in this research are regression, correlation analysis, coefficient of determination and hypothesis testing.